Evaluation of urban communication systems in their planning stage / Miesto susisiekimo sistemos planammo sprendinių įvertinimo problema - Juškevičius, P. (Journal of Civil Engineering and Management, 1996)
Based on standard requirements or subjective criteria, the traditional evaluation is not suitable for a qualitative planning of urban communications. The article deals with the main aspects of the problem (the content and the systematic complexity of criteria, their financial expression, the principles of evaluation). Also, some methods are suggested for applying as additional means when looking for economically and functionally acceptable urban communication solutions.Article in Lithuanian.First Published Online: 26 Jul 2012